Economic-based residential flexible resource allocation in microgrid. (November 2021) - Guo, Zishan; Guo, Hanhui; Hu, Qinran; Quan, Xiangjun; Wang, Qi; Wu, Zaijun
Abstract: As the penetration of distributed renewable generation increases, their intrinsic uncertainty and random raise neutral concerns on the reliability of microgrid. Demand side resources are considered helpful in facilitating the operation of microgrid. In recent years, the development of Internet of Things and electric vehicle enables the capability of residential demands serving as flexible grid assets to provide various ancillary services and enhance operation reliability. For the residential flexible resource, their control modes and subsidy prices greatly affect the performance and operation cost, and different resources, such as air conditioner and electric vehicle (distributed energy storage), have considerably different flexible capability, capacity and quantity. Thus, this paper provides an economic-based resource allocation model for residential flexible resources. The proposed model finds the cost-effective plan about how to allocate residential flexible resources to enhance reliability of microgrid. Case studies are conducted on a modified IEEE 9-node network to illustrate the effectiveness of the proposed model.